Penerapan Internet Sehat dan Aman untuk Menanamkan Kebiasaan Bijak dalam Penggunaan Media Sosial pada Siswa SMP: Pengabdian - Arina Aftitrya Izzati; Slamet Bambanag Riyono (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the implementation of healthy and safe internet among eleventh-grade junior high school students and to formulate effective educational strategies to minimize the negative risks of internet use among adolescents. The background of this study is based on the high dependence of students on the internet, both for learning and entertainment purposes, which on the one hand is useful in supporting the learning process but on the other hand has the potential to cause negative impacts such as addiction, exposure to age-inappropriate content, and cyberbullying. The study used a descriptive qualitative method with 30 eleventh-grade students in a public junior high school as research subjects, and involved ICT teachers, homeroom teachers, and parents as supporting informants. Data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed using thematic analysis techniques with source triangulation to ensure data validity. The results showed that almost all students used the internet daily for 3–6 hours, divided into academic and non-academic activities. Some students have demonstrated healthy internet behaviors such as verifying information before sharing it, but many still misuse the internet outside of school hours or access content without control. Schools have attempted to integrate digital literacy into the curriculum, but time constraints and academic priorities mean that healthy internet materials have not been taught optimally. Parents also face supervision challenges due to the digital literacy gap between generations. This study concludes that the successful implementation of a healthy and safe internet requires active collaboration between schools, parents, and students themselves, emphasizing participatory strategies so that students are involved in developing internet usage rules, thus developing critical awareness, digital ethics, and a sense of collective responsibility in building a safe and productive digital ecosystem.